Immediate breastfeeding and skin-to-skin contact during cesarean section decreases maternal oxidative stress, a prospective randomized case-controlled study. (17th August 2016) - Yuksel, Beril; Ital, Ilker; Balaban, Onur; Kocak, Emel; Seven, Ali; Kucur, Suna Kabil; Erbakirci, Mehmet; Keskin, Nadi
Abstract: Objective : Immediate skin-to-skin contact (ISSC) and early breastfeeding are recommended for the wellbeing of the neonate. In this study, we aimed to evaluate the effect of ISSC and early breastfeeding on maternal oxidative stress and postoperative pain. Methods : A total of 90 patients were randomized into two groups based on the timing of skin-to-skin contact and breastfeeding. Group 1 ( n  = 45) was provided ISSC and breastfeeding in the operating room during the cesarean section (C/S). Group 2 ( n  = 45) breastfed their babies 1 h after the C/S. As markers of oxidative stress, maternal serum levels of total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress indices (OSI) were evaluated. Maternal oxytocin levels and the relation between these parameters and postoperative pain were also evaluated. Results : The postoperative TAS levels were significantly higher, whereas TOS and OSI levels were lower in Group 1 than Group 2. Negative correlations between oxytocin level and postoperative TOS and OSI were observed, as was a positive correlation between oxytocin level and postoperative TAS. Conclusions : The effect of ISSC and early breastfeeding on mothers was documented for the first time in this study. Our results demonstrated ISSC and early breastfeeding during C/S reduce maternal oxidative stress.